Information Acquisition under Uncertainty in Credit Markets - Banerjee, Priyodorshi (Review of Financial Studies, 2005)
This article studies information acquisition through investment in improved risk assessment technology in competitive credit markets. A technology has two attributes: its ability to screen in productive borrowers, and its ability to screen out unproductive borrowers. The two attributes have fundamentally different effects on acquisition incentives and the structure of equilibrium informational externalities between lenders. The article also studies how uncertainty associated with the quality of superior technology affects information acquisition incentives. Uncertainty influences information acquisition even with risk-neutral banks. Increased uncertainty may raise or dampen incentives, depending on whether uncertainty is, respectively, about screening out or screening in quality.